Determination of the interfacial cohesive material law for SRG composites bonded to a masonry substrate. (April 2020) - Santandrea, Mattia; Focacci, Francesco; Mazzotti, Claudio; Ubertini, Francesco; Carloni, Christian
Highlights: SRG-masonry joints exhibit a scattered behavior associated with nature of matrix. Direct measurement of strain in the fibers to obtain CML is difficult in FRCMs. An indirect calibration of CML is proposed that employs the experimental responses. Fracture properties are independent of CML shape if debonding load is used. Abstract: Fiber reinforced cementitious matrix (FRCM) composites, also known as textile reinforced matrix (TRM) composites, are a suitable alternative to fiber reinforced polymer (FRP) composites to strengthen reinforced concrete and masonry structures. In the toolbox of FRCMs, a recently-developed composite that employs high-strength steel fibers embedded in a hydraulic mortar is particular appealing for applications on historical masonry constructions. This type of composite is known as steel reinforced grout (SRG). In this paper, an extensive experimental work is presented. Single-lap shear tests are performed to study the debonding of SRG strips from a masonry substrate, which is the critical failure mode for strengthening applications. For SRGs, debonding typically occurs at the fiber-matrix interface. A large scatter of the experimental results is observed, which is related to the variability of hydraulic mortars and their ability to impregnate the fibers. Although strain gauges can be applied directly to the fibers to obtain the experimental strain profile along the fibers, because of the presence of the matrix these measurements are complex and in some cases not reliable. Thus, indirect method based on the global response of the test is proposed to obtain the interfacial properties.